2021
DOI: 10.3390/en14238054
|View full text |Cite
|
Sign up to set email alerts
|

Performance Analysis and Optimisation of a Solar On-Grid Air Conditioner

Abstract: Solar-powered air conditioners offer a high potential for energy-efficient cooling with a high economic feasibility. They can significantly reduce the energy consumption in the building sector, which is essential to meet the greater ambition of reducing greenhouse gas emissions by 80% in the EU by 2050. This paper presents a computational model development capable of simulating the behaviour of a photovoltaic-assisted heat pump in different locations and working conditions. In addition, this model has been use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In some cases, for example, use of PV-air conditioner might reduce over 75% of grid electrical power for airconditioning in office building during daytime [1][2][3]. However, in hot country such as Thailand, the PV module temperature might reach 70 o C or more in the afternoon then the electrical efficiency was reduced significantly and only 75% or less of the power at standard condition could be generated [4][5][6][7], then many approaches to control the module temperature were presented. Sun et al [8] and Biwole et al [9,10] used phase change material (PCM) such as paraffin embedded at the rear surface of PV module and the module temperature was controlled and approaching to the PCM melting point during daytime.…”
Section: A Pvmentioning
confidence: 99%
“…In some cases, for example, use of PV-air conditioner might reduce over 75% of grid electrical power for airconditioning in office building during daytime [1][2][3]. However, in hot country such as Thailand, the PV module temperature might reach 70 o C or more in the afternoon then the electrical efficiency was reduced significantly and only 75% or less of the power at standard condition could be generated [4][5][6][7], then many approaches to control the module temperature were presented. Sun et al [8] and Biwole et al [9,10] used phase change material (PCM) such as paraffin embedded at the rear surface of PV module and the module temperature was controlled and approaching to the PCM melting point during daytime.…”
Section: A Pvmentioning
confidence: 99%
“…Photovoltaic systems with heat pumps are mainly considered for grid-tied cases [20,21] or stand-alone with battery storage backup [22]. The latter takes half CAPEX and an even greater share of TCO, so it is highly important to reduce this component once possible.…”
Section: Introductionmentioning
confidence: 99%
“…The climate and energy strategy adopted by the European Union assumes that by 2030 greenhouse gases emission will be reduces by 40% (to the level from 1990), while the energetic efficiency will be improved by at least 32.5% [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The construction and service sectors are of key importance for achieving these goals [1,2]. The carried-out review of the scientific literature regarding research into modelling the electrical energy consumption in buildings [2,3], including schools [4] or office buildings [5,6], confirmed that the topic is up-to-date, but no publications concerning models of automated stores have been found.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation